(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article provides brief information about welding joints used in machine building today. We also gave brief information about the types of welded joints, their advantages, places of use, and defects that occur in them. We calculated the tension forces in welded joints through the loadings generated at the welds of welded joints and their calculation expressions, and recommendations on the length of the weld and the methods of joining given.